Pengaruh Superleadership terhadap Self-leadership dan Kinerja Karyawan (Studi pada PT Perkebunan Nusantara V Riau) - Marnis, Marnis (Jurnal Aplikasi Manajemen, 2011)
The purpose of this study is to examine the effect of Superleadership on Self leadership employee's performance. Superleadership is expected relationship to improve Self leadership and employee's performance. It is also expected that, improve Self leadership is expected relationship to improve employee's performance. The population of this study is the employee of PTPN V in Riau, who has a position at middle manager. Using a sample of 146 middle manager, Sampling technique of the census method, the author tested structural equation modeling (SEM). All data of the respective measurement items are tested with reliability and validity test based on Alpha Cronbach to the internal consistence by using SPSS program version 16. To analyze the structural equation model, the study uses LISREL 8,70. The result of this study has un important meaning to PT Perkebunan Nusantara V Riau and also to The Plantation of The State Owned Enterprise. This study results a finding that the superleadership and self leadership of the middle manager will increase the employee's performance.